PERAN ARSIPARIS DALAM MENDUKUNG SISTEM ADMINISTRASI RUMAH SAKIT DI ERA MODERN - Indah Rosada Aini; Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2026)
This study aims to analyze the role of archivists in supporting hospital administrative systems within the modern digital era, specifically focusing on the quality of archives and its influence on operational efficiency. As healthcare institutions transition to electronic medical records, the archivist's function has expanded to include information governance. Using a qualitative descriptive approach through literature review, this research identifies that high-quality archives defined by accuracy, accessibility, and integrity significantly improve administrative response times and clinical decision-making. The study concludes that professional archivists are crucial in ensuring data quality, which directly impacts the overall quality of hospital services.